2020
DOI: 10.1111/1746-692x.12290
|View full text |Cite
|
Sign up to set email alerts
|

Can Small French Farms Provide an Opportunity for Employment in the Agricultural Sector?

Abstract: Les petites exploitations agricoles françaises peuvent-elles offrir une opportunité d'emploi dans le secteur agricole ? Können französische kleinbäuerliche Betriebe eine Chance für Beschäftigung im Agrarbereich bieten?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The study findings and their implications are important in the broadest context of subsistence and semi-subsistence farming [90,91] in their transformation toward farm entrepreneurship based on products of higher added value [83,92,93]. The findings can also be important for better understanding of changes in socioeconomic types of farms with part-time farming [94], which was important in the studied rural areas in the past with a combination of work in local labor-intensive factories and afternoon work on the farm.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The study findings and their implications are important in the broadest context of subsistence and semi-subsistence farming [90,91] in their transformation toward farm entrepreneurship based on products of higher added value [83,92,93]. The findings can also be important for better understanding of changes in socioeconomic types of farms with part-time farming [94], which was important in the studied rural areas in the past with a combination of work in local labor-intensive factories and afternoon work on the farm.…”
Section: Discussionmentioning
confidence: 72%
“…They can play an important role in farm and rural entrepreneurship and in short supply chains [79][80][81]. Small farms traditionally associated with subsistence or semi-subsistence farms can be entrepreneurially and commercially oriented and can play a role in the provision of public goods supported by public policies [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Some entrants reported that they obtained financing by borrowing from other well‐known entrepreneurs or family members, or, at later stages, by applying for small grants from business support programmes. For financial reasons, some newcomers combined two occupations during the first years of conversion; the previous job with the new engagement and in rare cases the farming has remained a part‐time activity combining various employment regimes (see also Lecole, 2021). Here, the second income source – both of the farmer and the spouse – is based on a side employment in the IT sector or accounting, allowing support for the farm in case of unforeseen challenges.…”
Section: Innovation Challengesmentioning
confidence: 99%